STRENGTHENING STUDENT WELL-BEING IN ISLAMIC BOARDING SCHOOLS BASED ON THE POSITIVE EDUCATION PERSPECTIVE - Moh. Maqbul Mawardi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
Student well-being is an element that students must own, this functions in increasing positive emotions, developing academies, improving relationships, improving mental health and developing a sense of responsibility for what they have decided. Islamic Boarding School is an Educational Institution that educates 24 hours. Islamic boarding schools in this study do not just provide academic education but also develop emotional abilities and build students' morals and character. This study aims to discover how to strengthen student wellbeing in Islamic boarding schools by studying it based on positive education. This research uses a literature research methodology. This study found that student wellbeing is embedded in some activities during 24 hours of education in Islamic boarding schools. The application process is reflected in students' characteristics, such as honesty, high discipline, paying attention to personal and environmental hygiene, mutual care, independence, hard work, politeness, responsibility, and development of creativity. While this is instilled in students through several stages: 1) knowing the rules, 2) action, and 3) habituation. Strengthening the welfare of students in Islamic boarding schools adopts the five elements of positive education called PERMA (positive emotion, engagement, relationship, meaning, and achievement). Similarly, in its application, positive education is implemented in some stages, 1) studying it, 2) teaching it, and 3) embedding it.